Penggunaan ChatGPT Sebagai Variabel Moderasi Pada Kecurangan Akademik Mahasiswa: Sebuah Tinjauan Fraud Pentagon - Hidayat, Rahmad Wahyu; Sangka, Khresna Bayu (Jambura Economic Education Journal, 2025)
This inquire about points to decide the impact of the extortion pentagon, specifically weight, opportunity, rationalization, capacity, and pomposity on scholarly extortion and the utilize of ChatGPT is able to direct the impact of the extortion pentagon, to be specific weight, opportunity, rationalization, capacity, and self-importance on scholarly extortion. This investigate employments quantitative strategies with a graphic approach. The populace in this think about were 40,707 understudies. The inspecting strategy utilized Nonprobability Examining with Purposive Examining with a test of 387 understudies and information collection strategies utilizing surveys. The legitimacy test employments Pearson relationship item minute and the unwavering quality test employments Cronbach Alpha. The investigate information examination strategy employments clear insights, numerous direct relapse examination, Directed Relapse Examination, t test, and the coefficient of assurance. The results of the following research explain that arrogance and pressure have no effect on academic fraud. However, rationalization, opportunity, ability have an influence on academic fraud. The intensity of using ChatGPT can moderate the influence of the fraud pentagon of opportunity, pressure, ability, rationalization, and arrogance on academic fraud.